An Active Catalyst System Based on Pd (0) and a Phosphine-Based Bulky Ligand for the Synthesis of Thiophene-Containing Conjugated Polymers - Liu, Meifang; Liu, Li; Zhang, Zhihui; Wan, Meixiu; Guo, Huanmei; Li, Dan (Frontiers in Chemistry, 2021)
To address the limitations of conventional Pd catalysts in the polymerization of thiophene-containing conjugated polymers, an active catalyst system based on Pd (0) and a phosphine-based bulky ligand, L1, is explored systematically in Suzuki–Miyaura polymerizations using thiophene boronic acid pinacol ester as one of the monomers. This active catalyst is found very efficient in synthesizing a series of thiophene-containing linear and hyperbranched conjugated polymers. First, as a model example, coupling reactions between electron-rich/moderately hindered aryl or thienyl halides and thiophene boronic acid pinacol ester give excellent yields with lower catalyst loading and can be completed in a shorter reaction time relative to Pd(PPh3)4. Notably, high molecular weight thiophene-containing polymers are successfully synthesized by Suzuki–Miyaura polycondensation of 2,5-thiophene bis(boronic acid) derivatives with different dibromo- and triple bromo-substituted aromatics in 5–15 min.